The Adverse Consequences of Technostress on Strain and Turnover Intentions Among Auditors: The Mitigating Effect of Segmentation Mindset - Abir Dhaouadi; Anis Khedhaouria; Neila Boulila (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research question- Does technostress have an impact on burnout and turnover intentions among auditors? And does segmentation mindset moderate the relationship between technostress and turnover intentions? Motivation- Technostress became omnipresent in various occupations. Focusing on auditing setting in particular allows us to identify the impact of technostress on turnover intentions considered as a severe problem for audit companies. Examining the moderating role of segmentation mindset in the relationship between technostress and turnover intentions can help audit firms foster a segmentation culture to mitigate the impact of technostress on burnout and turnover intentions. Idea- This paper explores the moderating role of the segmentation mindset in the relationship between technostress creators and turnover intentions among Tunisian audit professionals. Data- Drawing on the transactional model of stress and coping, 290 valid responses were collected from Tunisian practicing financial auditors. Tools- An online survey was used to validate the proposed model. Findings- The results suggest that burnout fully mediates the association between technostress creators and turnover intentions. Second, the study supports the positive association between technostress creators and job burnout and between burnout and turnover intentions. Further analysis using the Hayes Process model reveals that the positive effect of technostress creators on turnover intentions is dampened for auditors who score high on segmentation mindset. Contributions- The results of this study provide empirical evidence that audit companies should promote practices to reduce levels of job burnout, which could decrease turnover intentions. Implementing segmentation strategies is of paramount importance since individual segmentation can alleviate the technological stress's detrimental effects on turnover intentions.
Keywords: M42; M15; 650; Technostress; Burnout; Turnover intentions; Segmentation mindset; Auditing